Akumulasi Melalu Perampasan dan Kemiskinan di Flores - Tolo, Emilianus Yakob Sese (UI Scholars Hub, 2016)
This article aims to explain the poverty in Flores by using a political economy perspective. Through qualitative research method by literature review, this article argues that poverty in the region is caused by the accumulation by dispossession through three main areas, namely the long colonial history, agrarian inequality, and the de- politicization of the masses. The long history of colonization has led to the change of the system of administration and the agrarian structure for the sake of the accumulation by dispossession. The agrarian inequalities facilitate the process of accumulation by dispossession. Just by relying on unorganized spontaneous resistances, the accumulation by dispossession is unstoppable and keeps escalating until today.